The Influence of Shopping Motivation, Self-Concept, and Reference Groups on the Consumptive Behavior of Generation Z Followers @discountfess - D.Salsabela Zein; Maulida Nurhidayati (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2026)
The development of digitalization and social media increases people's consumptive behavior through easy access to discount promotions. This phenomenon can be seen in @discountfess autobase accounts on platform X that share promo and discount information. This study aims to analyze the influence of shopping motivation, self-concept, and reference groups on the consumptive behavior of @discountfess followers. This study uses a quantitative method with an associative approach. The sampling technique used purposive sampling with a total of 100 @discountfess followers. The data were analyzed using multiple linear regression with the help of SPSS version 22. The results of the study showed that shopping motivation did not have a significant effect on consumptive behavior. Meanwhile, self-concept and reference groups have a significant positive effect on consumptive behavior. Simultaneously, shopping motivation, self-concept, and reference groups had a significant effect on consumptive behavior with an R Square value of 0.740.